2019
DOI: 10.4049/immunohorizons.1800026
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 4A Stabilizes Human Regulatory T Cell Phenotype via Plexin B1

Abstract: We previously reported that neuroimmune semaphorin (Sema) 4A regulates the severity of experimental allergic asthma and increases regulatory T (Treg) cell numbers in vivo; however, the mechanisms of Sema4A action remain unknown. It was also reported that Sema4A controls murine Treg cell function and survival acting through neuropilin 1 (NRP-1) receptor. To clarify Sema4A action on human T cells, we employed T cell lines (HuT78 and HuT102), human PBMCs, and CD4 + T cells in phenotypic and functional assays. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…As expected, WT Sema4A displayed a highly specific effect on Treg cells, as it increased the relative number of CD4+Foxp3+ cells among PBMCs from 3.96 ± 0.46% in cultures with medium only to 6.18 ± 0.58% in cultures with 100 ng of WT Sema4A (Figure 8A,C). At the same time, the M198A Sema4A mutant demonstrated a more modest effect on the relative number of Tregs to 6.07 ± 0.61% of The mutant proteins were tested for their stimulatory effect on Treg cells in PBMC cultures, as described previously [17]. As expected, WT Sema4A displayed a highly specific effect on Treg cells, as it increased the relative number of CD4+Foxp3+ cells among PBMCs from 3.96 ± 0.46% in cultures with medium only to 6.18 ± 0.58% in cultures with 100 ng of WT Sema4A (Figure 8A,C).…”
Section: Effect Of Mutations In Sema4a On Binding To Plexin B1 and Tr...mentioning
confidence: 99%
“…As expected, WT Sema4A displayed a highly specific effect on Treg cells, as it increased the relative number of CD4+Foxp3+ cells among PBMCs from 3.96 ± 0.46% in cultures with medium only to 6.18 ± 0.58% in cultures with 100 ng of WT Sema4A (Figure 8A,C). At the same time, the M198A Sema4A mutant demonstrated a more modest effect on the relative number of Tregs to 6.07 ± 0.61% of The mutant proteins were tested for their stimulatory effect on Treg cells in PBMC cultures, as described previously [17]. As expected, WT Sema4A displayed a highly specific effect on Treg cells, as it increased the relative number of CD4+Foxp3+ cells among PBMCs from 3.96 ± 0.46% in cultures with medium only to 6.18 ± 0.58% in cultures with 100 ng of WT Sema4A (Figure 8A,C).…”
Section: Effect Of Mutations In Sema4a On Binding To Plexin B1 and Tr...mentioning
confidence: 99%
“…Mouse NRP1 is a critical receptor for Sema4A acting on Treg cells to regulate their stability and function (Delgoffe et al 2013 ). In humans, Plexin B1 plays this Sema4A-dependent potentiating function for Treg cells which lack NRP1 expression (Chapoval et al 2019 ). NRP1 is also expressed on CD4 low PBMC-derived human monocytes (Chapoval et al 2019 ).…”
Section: Nrp1 Structure and Functionmentioning
confidence: 99%
“…In humans, Plexin B1 plays this Sema4A-dependent potentiating function for Treg cells which lack NRP1 expression (Chapoval et al 2019 ). NRP1 is also expressed on CD4 low PBMC-derived human monocytes (Chapoval et al 2019 ). Therefore, these monocytes might potentially get infected with SARS-CoV-2 virus although the ACE-2 expression on these cells has not been assessed.…”
Section: Nrp1 Structure and Functionmentioning
confidence: 99%
“…Sema4A is mainly produced by dendritic cells, monocytes and macrophages [ 11 ], although it can be also expressed by activated CD4 + T cells and germinal center B cells [ 12 , 13 , 14 ]. Sema4A binds to different receptors expressed on CD4 + T cells, such as PlexinB1, PlexinB2, PlexinD1, Neuropilin-1 (NRP-1), Immunoglobulin-like transcript 4 (ILT)4 and Tim-2, although the last has been reported in mice and has no human orthologous [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Several studies have shown that Sema4A expression is elevated in diseases in which Th cells play an essential role, including asthma, RA, MS and SSc [ 11 , 12 , 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%